Resistência das chapas laterais de silos metálicos utilizando novo modelo de parafuso - Ficanha, Daniele Cristina (2020)
Metal silos are used to store and preserve grain quality. Thus, proper sizing is of utmost importance, in order to guarantee the efficiency and safety of the equipment. The possibility of implanting a metallic silo is based mainly on the cost and weight of the raw material: steel. The side plates represent most of the raw material used. The possibility of the alternative screw by Ficanha (2016), responsible for the connections of the elements of the silo body, increases the resistance of the side plate. Considering such, the possibility of ways to increase the strength of these plates together with the screw connection becomes attractive and economical. Through the alternative screw, capable of supplying the project requests, a new concept of structural design and assembly system for the side plates is brought about. The theoretical analysis started by optimizing the screw connection with the alternative screw and replicated for the traditional screw, analyzing the possible models according to the recommendations of NBR 14762 (ABNT, 2010). The strength of the thin steel plate set screwed with the alternative screw was higher in all thicknesses between 0.80 and 6.70 mm, when compared to the traditional screw. Connections with single and double seam are not possible for use in metallic silos due to the loss of resistance in the connections. In view of the four rupture models, triple stitching is the ideal one. The quadruple seam increases the strength of the set, but other breaks occur before the shear of the screws. For experimental tests of the 0.92 and 3.00 mm sets, the mean of the model error random variable indicated a safe and conservative experimental behavior. The reliability of the results raised the theoretical dimension between 28 and 34%, using the current regulations, even disregarding the weighting coefficients of the actions. The Ct values obtained normatively also remained conservative. The ruptures of the 0.92 mm samples by crushing were not consistent with the normative model of rupture of the liquid section in the connection region. For the 3.00 mm samples, the theoretical phenomenon was confirmed with the rupture of the liquid section in the connection region.In order to explain the experimental results obtained in this research, mathematical expressions are proposed for the rupture models of the liquid section in the connection region and rupture by crushing. The alternative screw becomes a possible solution in the screw connections of the metal plates used in the side of the silos.